DiAngelo Robin J. White fragility: why it’s so hard to talk to white people about racism. Description: Boston: Beacon Press, [2018]. Рец. Н.Н. Мещерякова; Социологические исследования; № 9 - Мещерякова Н. Н. Наталия Николаевна (2020, 2020)
Заглавие с экрана